Entre fragmentation et ordre urbain : une géographie politique des espaces de l’entre-soi - Christophe Mager; Laurent Matthey (L'Espace Politique)
Instituted in a circulation and a hybridization of the architectural models, the urban forms relate topolitical geography. Spaces of togethernessconstitute good examples of these circulation and hybridization logics: from the fashionable London districts to its upsurge in France, this form knew various contributions, enrichments and acclimatizations (Matthey & Gaillard, 2011) which gradually propelled it to the status of “generic real estate product” (Bagaeen & Uduku, 2010).  But if they concern political geography, it is also because these spaces of togethernessare at the same time relevant analysers and powerful operators of the policy reconfigurations of the urban ensembles. The contributions of this thematic issue of L’Espace politique take precisely place in this urban geopolitics context.